Next-generation humanized NSG-SGM3 mice are highly susceptible to Staphylococcus aureus infection - Hung, Sophia; Kasperkowitz, Amelie; Kurz, Florian; Dreher, Liane; Diessner, Joachim; Ibrahim, Eslam S.; Schwarz, Stefan; Ohlsen, Knut; Hertlein, Tobias (Frontiers in Immunology, 2023)
Humanized hemato-lymphoid system mice, or humanized mice, emerged in recent years as a promising model to study the course of infection of human-adapted or human-specific pathogens. Even though Staphylococcus aureus can infect and colonize a variety of species, it became nonetheless one of the most successful human pathogens of our time with a wide armory of human-adapted virulence factors. Humanized mice showed increased vulnerability to S. aureus compared to wild type mice in various clinically relevant disease models. Most of these studies employed humanized NSG (NOD-scid IL2Rgnull) mice which are widely used in the scientific community, but show poor human myeloid cell reconstitution. Since this immune cell compartment plays a decisive role in the defense of the human immune system against S. aureus, we asked whether next-generation humanized mice, like NSG-SGM3 (NOD-scid IL2Rgnull-3/GM/SF) with improved myeloid reconstitution, would prove to be more resistant to infection. However, to our surprise, we found the contrary when we challenged humanized NSG-SGM3 (huSGM3) mice with S. aureus: although they had stronger human immune cell engraftment than humanized NSG mice, particularly in the myeloid compartment, they displayed even more pronounced vulnerability to S. aureus infection. HuSGM3 mice showed overall higher numbers of human T cells, B cells, neutrophils and monocytes in the blood and the spleen. This was accompanied by elevated levels of pro-inflammatory human cytokines in the blood of huSGM3 mice. We could furthermore elucidate that the impaired survival of huSGM3 mice was not linked to higher bacterial burden nor to differences in the murine immune cell repertoire. On the other hand, we could demonstrate a correlation of the rate of humanization and the severity of infection. Collectively, this study suggests a detrimental effect of the human immune system in humanized mice during the encounter with S. aureus and might help to guide future therapy approaches and analysis of virulence mechanisms.